2021
DOI: 10.1002/tesj.583
|View full text |Cite
|
Sign up to set email alerts
|

Teacher language practices that support multilingual learners: classroom‐based approaches from multilingual early childhood teachers

Abstract: WAGNER is at and slightly above learners' ability plays a central role in effective language instruction for children (Dubiner, 2019;Krashen, 1985). The quality use of home languages to explain and discuss ideas is connected to increased vocabulary learning in the home language, with potential benefits to English language learning (Hindman & Wasik, 2015). The use of children's home languages likewise plays a role in literacy learning, with the increased use of these languages by the teacher linked to higher re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…Dock har studier i detta perspektiv där alla inte delar majoritetsspråket varit begränsade. I det fall vi studerat här kan förskolläraren själv mer än ett språk, men de strategier hon använder förefaller delvis även kunna Inledningsvis pekades mot att förskolan och den narrativa leken där barn och vuxna gemensamt deltar är ett potentiellt translanguaging space (Li, 2011) och där förskollärares förhållningssätt, intresse och kompetens gällande flerspråkighet är avgörande för kvaliteten (Wagner, 2021). Denna studie styrker att leken kan utgöra en arena för translanguaging där deltagarna tillsammans skapar mening och använder sina språkliga repertoarer på kreativa sätt.…”
Section: Diskussion Och Slutsatserunclassified
See 1 more Smart Citation
“…Dock har studier i detta perspektiv där alla inte delar majoritetsspråket varit begränsade. I det fall vi studerat här kan förskolläraren själv mer än ett språk, men de strategier hon använder förefaller delvis även kunna Inledningsvis pekades mot att förskolan och den narrativa leken där barn och vuxna gemensamt deltar är ett potentiellt translanguaging space (Li, 2011) och där förskollärares förhållningssätt, intresse och kompetens gällande flerspråkighet är avgörande för kvaliteten (Wagner, 2021). Denna studie styrker att leken kan utgöra en arena för translanguaging där deltagarna tillsammans skapar mening och använder sina språkliga repertoarer på kreativa sätt.…”
Section: Diskussion Och Slutsatserunclassified
“…Forskning pekar mot att avgörande faktorer för att leken ska bli denna viktiga arena för språkutveckling i förskolan är personalens förhållningssätt och kompetens gällande flerspråkighet i förskolan samt att de visar intresse för flerspråkighet (t.ex. Wagner, 2021). Vuxna har visat sig kunna stötta barn i gemensamma narrativa lekar genom att bidra på skilda sätt; ta initiativ till narrativets utveckling och respondera på barns skilda uttryck (Pramling et al, 2019).…”
Section: Introduktionunclassified
“…Within the field of literacy instruction, there continues to be a need to better prepare literacy teachers to work with young multilingual learners, including how multilingual teachers can use their multilingualism to support language learning (Langeloo et al, 2019). In this example, OTI was used to provide a field-based learning experience for multilingual early childhood teachers to improve their use of multiple languages in the classroom (see Wagner, 2021a;Wagner, 2021b). Throughout the OTI programme, teachers were asked to consider how they, as multilingual teachers, make instructional choices about when and how to draw on their own multilingualism to support children's learning.…”
Section: Context and Participantsmentioning
confidence: 99%
“…Finally, multilingual teachers can be particularly valuable allies in this advocacy work. Teachers participating in professional learning programs on using multilingual practices in classrooms reported that as multilinguals themselves, they felt uniquely positioned to understand the dynamics of multilingualism inside and outside of the classroom (Wagner, 2020b). These teachers drew on their professional knowledge about language development and their own personal histories as multilingual learners to engage with multilingual families in language planning.…”
Section: Collaborative Language Planning As Advocacy Workmentioning
confidence: 99%